If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -4x = 1 + -1x Solving -8 + -4x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -8 + -4x + x = 1 + -1x + x Combine like terms: -4x + x = -3x -8 + -3x = 1 + -1x + x Combine like terms: -1x + x = 0 -8 + -3x = 1 + 0 -8 + -3x = 1 Add '8' to each side of the equation. -8 + 8 + -3x = 1 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 1 + 8 -3x = 1 + 8 Combine like terms: 1 + 8 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| x-15=4x | | 16x+8-12x+6=18x+9 | | 7n=2n-20 | | y^2=x^3+9x+17 | | a+(5+3a)=2a-7 | | 4(2x+3)=2(5x-2)+6 | | 9-6y=24-8y+7 | | 3t^2=6t-12 | | 4y-7+2y=5y-6+9 | | 13-2x= | | x-5y=3v | | 2x+5=3x+10 | | 3a-4=A | | 2x-20=5x-5 | | 189-5x=31x+17 | | -35-4x=13-10x | | 51-3x=7x+21 | | 6x+14=91-5x | | 6x+36=14x-52 | | (6x-5)(6x-5)=36x-25 | | 2a+2b+2c=262 | | 2n-20=7n | | 6x^2-10x+1=0 | | 19-3=x-8 | | 54x+15=16 | | 4=3x-10+x-2 | | 15-6(2x-5)=50 | | -7x-12=-3x-16 | | 3x+3=5x-11 | | x+12=5x-16 | | 24-5y=3(10-y) | | -x^4+13x^2-3=0 |